(untitled) (Agro Productividad, 2023)
Objective: To infer the role of multifunctionality in the milpa systems of the Mixteca Alta region of Oaxaca, Mexico. Design/Methodology/Approach: The methodological framework of the Multifunctionality Index of Agricultural Production Systems (IMSPA) was used, applying semi-structured interviews to producers. Results: The multifunctionality level of each evaluated systems was determined and the Milpa Intercropped with Fruit Trees (MIAF) showed the greatest multifunctionality and potential attributes for local development. Study Limitations/Implications: The resistance among producers to make changes in their plots usually leads to a refusal to participate and to mistrust this type of research. Findings/Conclusions: It is necessary to follow up on multifunctionality evaluations, since some systems are at a point where their functions can advance or regress.